Strategi Pembelajaran strategi pembelajaran tematik tepadu: MIN I Bondowoso - baitullah, rachmad (IJIT: Indonesian Journal of Islamic Teaching, 2019)
ABSTRACT Rachmad Baitullah, 2018. Integrated Thematic Learning Strategy at MIN I Bondowoso. Thesis. Teacher Education of Madrasah Ibtidaiyah Postgraduate of State Institute of Islamic Studies Jember. Advisor I: Dr. Hj. Mukni'ah, M.Pd.I. Advisor II: Dr. H. Saihan, M.Pd.I Keywords: Learning Strategies, Integrated Thematic Integrated thematic learning is a learning approach that integrates various competencies from several subjects or several disciplines that are incorporated into one particular theme with a meaningful learning process, according to student development. Through thematic learning teachers will try to improve the students integrity so that there will be treatment of wholeness (self-confidence), honesty and sincerity, integrity is needed to distinguish which is allowed and which is not allowed. If the teacher has succeeded in instilling and increasing the level of integrity, it means that it has been able to improve the quality of life, even though integrity is individual need to have a rational touch. The focuses of this study were: 1) How is the plan of Integrated Thematic learning at MIN I Bondowoso;2) How is the implementation of Integrated Thematic Learning at MIN I Bondowoso; and 3) How is the evaluation of Integrated Thematic Learning at MIN I Bondowoso. While the purpose of this study was to describe: 1) the planning of Integrated Thematic learning at MIN I Bondowoso; 2) the implementation of Integrated Thematic Learning at Bondowoso I MIN; and 3) Evaluation of Integrated Thematic Learning at MIN I Bondowoso. The theories used in this study are Harold Koontz about the scientific approach, while Bruner, Piaget and Vigotsky regarding the characterization of authentic assessment and Darling Hammond about authentic assessment. This study used a qualitative approach, with qualitative descriptive methods. The type of this study used phenomenology, meaning that this research seek to understand the meaning of events and their relation to people in certain situations. The selection of research subjects was purposive. Data collection techniques used Observation, Interview and Documentation. Data analysis techniques in this research used the interactive analysis techniques of Miles and Huberman models include data collection, data reduction, data presentation and conclusions. While the validity of the data was strengthened by triangulation techniques and member checks. Triangulation used included source and technique triangulation. The conclusions of this study were: 1) Planning was developed every year based on training results, PGSD undergraduate courses, discussions, guidance by using mapping, developing syllabus and lesson plans, reviewing indicators, understanding material characteristic by using methods, applying appropriate approaches according to the characteristics of participants students, determine suitability of learning objectives with basic competencies and characteristics of learning materials, analyze various components of learning to determine models, approaches, strategies, methods, steps and learning steps, establish norms, minimum limits of success and standard rules, and determine appropriate types, techniques and forms of assessment; 2) The implementation of integrated thematic learning referred to the Learning Plan, analyzed used scientific learning, used fun and developed teaching aids, prepared classroom and media, communicated competencies; and 3) Integrated thematic learning evaluation was planned and discussed together, including the processes and the results by using tests (written and oral tests) and non tests (performance, projects and portfolios). It was held at the beginning of learning, during learning, end of learning, midterm, end of semester and end of school. Meanwhile, the success of learning was celebrated through inauguration of graduation at the end of the year. The assessment was done to obtain the description of the success of the process and achievement of competency mastery using integrated thematic approach at MIN I Bondowoso in the form of daily assessments, midterm assessments, final assessments, final madrasah assessments, and national assessments by using both oral and written test to assess the achievement of cognitive, performance, project, portfolio and journal competencies and the success of evaluations with graduation processions at the end of the year.